If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = -3(4x + 6) Reorder the terms: 3 = -3(6 + 4x) 3 = (6 * -3 + 4x * -3) 3 = (-18 + -12x) Solving 3 = -18 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 3 + 12x = -18 + -12x + 12x Combine like terms: -12x + 12x = 0 3 + 12x = -18 + 0 3 + 12x = -18 Add '-3' to each side of the equation. 3 + -3 + 12x = -18 + -3 Combine like terms: 3 + -3 = 0 0 + 12x = -18 + -3 12x = -18 + -3 Combine like terms: -18 + -3 = -21 12x = -21 Divide each side by '12'. x = -1.75 Simplifying x = -1.75
| y=(x^3-6x^2-x+6)(x^2-2x+5) | | 6/-16 | | 3x-12=4x+2-x | | 2x-4=-x-5 | | e^5x=26 | | 5[x-6]+2=7x-6 | | 7c+2=31 | | -2x-12=-6(2+6n) | | y=(x-6)(x^2-1) | | 3(2x-5)-6(2x-6)= | | 1/2×-3=11 | | (3a-1)+(2a+1)+(5a-2)=28 | | 4d-45d=-8 | | 4(-7x+8)=3x+32 | | 36/60=x/100 | | -5x+5=2x-16 | | 3a-1=x | | 77.50=0.15x+10 | | x^2-.2x+0.05=0 | | -1-n=-4(3n+3) | | 5x+12-x=12+4x | | 36/200 | | Y-9=(11/4)x-2 | | 3c-5=2c+50 | | 3-2(2x-3)+3(4x-1)=-20 | | 6x+3=-5x+7 | | 7x-5=8x-14 | | (u+4)(u+4)=2u^2+17u+34 | | 6x+3=-5x+-7 | | 2x-3y-2z=4x+3y | | m/s | | -8x-x+5=14 |